2016
DOI: 10.1371/journal.pgen.1005876
|View full text |Cite|
|
Sign up to set email alerts
|

Combating a Global Threat to a Clonal Crop: Banana Black Sigatoka Pathogen Pseudocercospora fijiensis (Synonym Mycosphaerella fijiensis) Genomes Reveal Clues for Disease Control

Abstract: Black Sigatoka or black leaf streak disease, caused by the Dothideomycete fungus Pseudocercospora fijiensis (previously: Mycosphaerella fijiensis), is the most significant foliar disease of banana worldwide. Due to the lack of effective host resistance, management of this disease requires frequent fungicide applications, which greatly increase the economic and environmental costs to produce banana. Weekly applications in most banana plantations lead to rapid evolution of fungicide-resistant strains within popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 120 publications
4
129
0
Order By: Relevance
“…An analysis of several isolates of P. fijiensis has also revealed allelic variation in some of the effector‐coding sequences (Stergiopoulos et al ., ). These findings further strengthen the radiative evolution theory for the Pseudocercospora banana pathogens (Arango‐Isaza et al ., ). With this information and knowledge of gene expansions in these pathogens, gene validation studies could be further intensified to gain more insight on gene function in the Pseudocercospora banana pathogens (Santana et al ., ).…”
Section: Advances In Genomics Of Pseudocercospora Banana Pathogensmentioning
confidence: 97%
See 4 more Smart Citations
“…An analysis of several isolates of P. fijiensis has also revealed allelic variation in some of the effector‐coding sequences (Stergiopoulos et al ., ). These findings further strengthen the radiative evolution theory for the Pseudocercospora banana pathogens (Arango‐Isaza et al ., ). With this information and knowledge of gene expansions in these pathogens, gene validation studies could be further intensified to gain more insight on gene function in the Pseudocercospora banana pathogens (Santana et al ., ).…”
Section: Advances In Genomics Of Pseudocercospora Banana Pathogensmentioning
confidence: 97%
“…These efforts have resulted in the identification of gene homologues associated with P. fijiensis virulence (Cho et al ., ; De Wit et al ., ; Stergiopoulos et al ., ). Later, the genomes of P. fijiensis isolates CIRAD86 and CIRAD139 were sequenced using Sanger and Illumina Hi Seq technologies, and have provided more detailed information on genomic structure and content, as well as the functionality of several genes in the pathogen (Ohm et al ., ; Arango‐Isaza et al ., ). These studies have clearly demonstrated genome expansion in P. fijiensis by the presence of repetitive sequences; such expansion may possibly be a result of horizontal gene transfer from banana or from other fungi colonizing banana (Friesen et al ., ; Arzanlou et al ., ; Ma et al ., ; Santana et al ., ; Czislowski et al ., ).…”
Section: Advances In Genomics Of Pseudocercospora Banana Pathogensmentioning
confidence: 98%
See 3 more Smart Citations